Select-response grouping proof and its verification protocol for RFID tags. (10th March 2011) - Lien, Yuan-Hung; Leng, Xuefei; Mayes, Keith E.; Chiu, Jung-Hui
In this paper, we investigate an application scenario in which the user requires a proof that a group of radio frequency identification (RFID) tags are scanned simultaneously by reading devices. Such a proof is generally called a grouping proof. After examining the existing 'yoking proof' grouping protocols used for RFIDs, an improved protocol called the 'select-response' grouping proof is proposed. Instead of passively awaiting the responses from RFID tags as used in existing protocols, the proposed protocol uses a new mechanism whereby the reader/verifier actively sends commands to each tag, asking for a response and then generating the grouping proof. After this fundamental change, the verification process is simple and flexible. In addition, the proposed protocol can perform multi-group verification and it also possesses collision-free, missing tag identification, and reading order independent properties. Moreover, the proposed protocol protects the mutual authentication from clandestine scanning and replay attacks, and hence, the overall security is improved.